PENGARUH BIAYA BAHAN BAKU DAN HARGA JUAL TERHADAP LABA PADA HOME INDUSTRI SARI BUMI - heryadi, rendi (Jurnal Ilmu Akuntansi, 2022)
This study aims to determine whether or not there is an effect of raw material costs, selling prices on profits that arise due to the increase in soybean raw materials in the market, this research is a quantitative study. Raw materials are costs that must be incurred by a company in order to obtain raw materials for later use in the production process. The selling price is the price determined and charged to consumers which is obtained or calculated from the entire cost of the production process plus non-production costs plus the profit expected by the company. The profit that the company hopes for is a benchmark for the company to see how well the company is performing for the sake of the company's survival. The company in this study is a manufacturing company where the company is a company that produces raw materials until the materials are ready for sale. This company produces tofu which is made from soybeans. The population taken in this study is the purchase of raw materials which are included in production costs and profit and loss statements at the company as many as 72 samples. The sample in this study is the cost of raw materials, selling price and income statement financial data taken for 6 years. The data analysis technique used in this study uses inferential statistics or also often referred to as inductive statistics. The research data is secondary data in the form of financial statements owned by the company in 2015-2021. The results of this study conclude that the cost of raw materials and selling prices partially have a significant effect on profits. The cost of raw materials has a significant effect on profit. The selling price partially affects the profit. Keywords: raw material cost, selling price and Profits